Revolutionary Scholarship Award Accuracy in Vocational High Schools with Decision Support Systems: Akurasi Penghargaan Beasiswa Revolusioner di Sekolah Menengah Kejuruan dengan Sistem Pendukung Keputusan - Sari, Novi Nur Malaita; Taurusta, Cindy (Indonesian Journal of Innovation Studies, 2023)
The aim of this research is to investigate the determination of scholarships at SMK Nasional Mojosari and to facilitate teachers in providing scholarships to deserving and high-achieving students, while also testing the quality of the system. The author uses the Waterfall method to build the system, which is a systematic and sequential approach that begins with analyzing, designing, coding, and testing the system. To analyze the system, several stages of data collection, problem formulation, user requirements, and concept analysis are required. The application design stage uses the CRISP_DM data mining model, and the testing stage uses the PIECES method. The accuracy of the Decision Tree classification for scholarships was determined using a confusion matrix, and the testing results showed an accuracy rate of 72.77% using RapidMiner. From these results, it can be concluded that the Decision Support System developed and tested is effective for processing and calculating data. Highlights: 1. The current process of determining scholarship recipients at SMK Nasional Mojosari is manual and time-consuming, which highlights the need for a more efficient and accurate system. 2. The author uses the Waterfall method, a systematic and sequential approach, to build a Decision Support System that facilitates the process of providing scholarships to deserving and high-achieving students while also testing the quality of the system. 3. The testing results showed an accuracy rate of 72.77% using RapidMiner, indicating that the Decision Support System is effective for processing and calculating data, and can help teachers make informed decisions about scholarship recipients.